Development and evaluation of a self-assembled nanoparticle-based prodrug for sustained delivery of 4-phenylbutyric acid - Kikka Maeda; Babita Shashni; Hirofumi Matsui; Yukio Nagasaki (Science and Technology of Advanced Materials)
4-Phenylbutyric acid (PBA) is a small molecule with promising therapeutic potential for treating various diseases, including cancer and neurodegenerative disorders, due to its dual ability to reduce endoplasmic reticulum stress and inhibit histone deacetylases. However, its clinical application is hindered by rapid clearance from the body, necessitating frequent dosing that increases the risk of adverse effects. To address these limitations, we developed a nanoparticle-based prodrug (NanoPBA) utilizing the amphiphilic block copolymer poly(ethylene glycol)-b-poly(vinyl 4-phenylbutyrate) [PEG-b-P(VPBA)]. This system self-assembles into micelles, enabling controlled and sustained PBA delivery. The synthesis and characterization of NanoPBA revealed its high stability under physiological conditions and enzyme-responsive PBA release. NanoPBA demonstrated a controlled release profile in vitro, reducing burst release while maintaining therapeutic efficacy. Cytotoxicity assays using normal cell lines, including endothelial cells (BAEC), macrophages (RAW264.7), and rat gastric cells (RGM-1), showed minimal cytotoxic effects compared to the parent low-molecular-weight PBA. Furthermore, in vivo studies conducted in healthy C57BL/6J mice confirmed NanoPBA’s biocompatibility, with no significant adverse effects observed at therapeutic doses ranging from 200 to 500 mg-PBA/kg via oral administration. In conclusion, NanoPBA offers a controlled release profile, enhanced biocompatibility, and reduced toxicity, addressing the limitations associated with conventional PBA administration. These attributes make NanoPBA a promising candidate for improving the therapeutic efficacy and safety of PBA in clinical applications, particularly in diseases where maintaining consistent drug levels is crucial for treatment outcomes.